Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Ta có:7x(2-3x)+x2(2x+1)-2x2(x-2)+2x(8x-7)
=14x-21x2+2x3+x2-2x3+4x2+16x2-14x
=(14x-14x)+(-21x2+x2+4x2+16x2)+(2x3-2x3)
=0
(6x9 - 2x6 + 8x3) : 2x3
= (6x9 : 2x3) + (-2x6 : 2x3) + (8x3 : 2x3)
= (3x6 - x3 + 4)
=> Chọn C. (3x6 - x3 + 4)
\(3-\left(x-1\right)=2-2\left(x-3\right)\)
\(3-x+1=2-2x+6\)
\(4-x=8-2x\)
\(4-x-8+2x=0\)
\(x-4=0\)
\(x=4\)
3-(x-1)=2-2(x-3)=>3-2=x-1-2(x-3)=>1=x-1-2x+6
=>1=-x+5=>-x=1-5=-4=>x=4
Chúc bạn học tốt nhớ k cho mik nha.
\(\frac{3}{2x}+\frac{3x-3}{2x-1}+\frac{2x^2+1}{4x^2-2x}\)
= \(\frac{3\left(2x-1\right)+2x\left(3x-3\right)+2x^2+1}{4x^2-2x}\)
= \(\frac{6x-3+6x^2-6x+2x^2+1}{4x^2-2x}\)
= \(\frac{8x^2-2}{4x^2-2x}\)
= \(\frac{2}{2x}\)
\(4x^2\left(3x-1\right)\)
\(=4x^2.3x+4x^2\left(-1\right)\)
\(=12x^3-4x^2\)